2010
DOI: 10.1158/1078-0432.ccr-09-1920
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of PD-0325901, an Oral MEK Inhibitor, in Previously Treated Patients with Advanced Non–Small Cell Lung Cancer

Abstract: Purpose: To evaluate the efficacy of mitogen-activated protein kinase/extracellular signal-related kinase kinase inhibitor PD-0325901 in advanced non-small cell lung cancer patients who had experienced treatment failure after, or were refractory to, standard systemic therapy.Experimental Design: This open-label, phase II study initially evaluated 15 mg PD-0325901 twice daily administered intermittently (3 weeks on/1 week off; schedule A). As this schedule was not well tolerated, a second schedule was introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
155
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(158 citation statements)
references
References 26 publications
(30 reference statements)
3
155
0
Order By: Relevance
“…However, a phase II clinical trial in advanced non-small cell lung cancer was negative for its primary endpoint, with no patients achieving partial or complete responses (23,24). These studies highlight the possibility that MEK inhibitors, as with PI3K pathway inhibitors, may need to be developed with alternate scheduling, appropriate patient selection criteria, or be combined with other rationally determined inhibitors to be clinically successful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a phase II clinical trial in advanced non-small cell lung cancer was negative for its primary endpoint, with no patients achieving partial or complete responses (23,24). These studies highlight the possibility that MEK inhibitors, as with PI3K pathway inhibitors, may need to be developed with alternate scheduling, appropriate patient selection criteria, or be combined with other rationally determined inhibitors to be clinically successful.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of the clinical development of PD-0325901 is that prolonged exposure can cause diarrhea and ocular toxicity (23)(24)(25); therefore, using the compound at a minimally effective dose rather than the maximum-tolerated dose may improve tolerability. This schedule was well tolerated, causing no weight loss over the treatment period (data not shown).…”
Section: Combined Inhibition Of Pi3k/mtor (Pf-04691502) and Mek (Pd-0mentioning
confidence: 99%
“…[10][11][12][13][14] We recently showed in preclinical studies that inhibition of ERK1/2 phosphorylation by 1st generation MEK and ERK inhibitors correlated with significant cell death in a lymphoma tumor model, 15 while others showed that sublethal concentrations of a 1st generation MEK antagonist potentiated the effect of sorafemib in lymphoma cells. 16 Furthermore, we recently demonstrated that MCT-1, an oncogene directly downstream of MEK/ ERK, is over-expressed in the majority of primary DLBCLs.…”
Section: Introductionmentioning
confidence: 99%
“…Phase II and III trials of single agent trametinib have suggested efficacy in patients with BRAF-mutated melanoma who had not received previous BRAF inhibitor therapy [6] but not in those patients resistant to BRAF inhibition. In contrast, a series of phase II studies of other MEK inhibitors have shown limited evidence of efficacy in numerous settings, including treatment of cancers with high known incidence of dysregulated MAPK signalling [21][22][23][24][25] and selection of individuals with known BRAF-mutated tumours [26]. It is, therefore, likely that this class of agents will be used in rationally chosen combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy with trametinib/dabrafenib and cobimetinib/vemurafenib for the treatment of BRAF-mutation positive melanoma has been shown to improve overall survival, and both these combinations are now licensed [8,12,27]. It has been suggested that resistance to MEK inhibition may occur via up regulation of AKT signalling and that combination therapy with both MEK and PI3K inhibitors may be beneficial [24,26], and investigations into this combination therapy continue [28]. The use of MEK inhibitors in combination with docetaxel has been investigated in phase II studies in melanoma [29] and NSCLC with indications that KRAS mutant NSCLC may be sensitive to the combination [30] and a phase III trial is underway to test the efficacy of the combination [31].…”
Section: Discussionmentioning
confidence: 99%